Shlapak L.S., Shihab Th.A., Prysyazhnyuk P.M. Lutsak L.D., Andrusyshyn R.V. Modelling of the heat transfer for the oil and gas centrifugal pumps seal faces made of composite based on chromium carbide during dry friction - Шлапак, Л. С.; Шіхаб, Т. А.; Присяжнюк, П. М.; Луцак, Л. Д.; Андрусишин, Р. В. (Problems of Tribology, 2018)
This article provides modelling of the heat transfer during dry friction regime of the mechanical seals rings of centrifugal pumps. The rings were made of composite material based on chromium carbide with copper-nickel-manganese binder by the powder metallurgy method which includes pressureless infiltration carbide skeleton by molten metal. Obtained heat transfer model based on the solving Fourier equation with considering the composite material structure features. Proposed model for heat transfer during friction can be used in oil and gas industry for rational material selection of centrifugal pumps mechanical seals rings at operation of which there is a risk of dry friction. Based on the simulation of the temperature field, which arises as a result of heat generation during dry friction, the nature of the heat distribution in the mechanical seals rings of centrifugal pumps was established. The calculations show that the most successful combination for mechanical seals rings is a pair of ceramics based on silicon carbide and metal ceramics based on the Cr3C2–Cu60–Ni20–Mn20 system, with estimated and experimental data at a high level of compliance. The obtained results allow to provide high reliability of the work of centrifugal pumps due to high resistance to thermal stresses that arise at the moment of the pump starts and (or) while disrupted operation mode.